PHYTOCHEMICAL AND PHYSICOCHEMICAL ANALYSIS OF MICROWAVE-ASSISTED EXTRACTION CORIANDRUM SATIVUM L. LEAVES AND ITS BIOLOGICAL EVALUATION - SAMREEN FATEMA; MAZAHAR FAROOQUI; PATHAN MOHD ARIF; SYED UMMUL KHAIR ASEMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the present work is to carry out the phytochemical constituent present and physicochemical analysis of microwave-assisted extract (MAE) of Coriandrum sativum leaves and to investigate its antibacterial activity. Methods: The powdered samples of the leaves were extracted and analyzed for physicochemical properties. Extraction was carried out for C. sativum using different solvents and used for phytochemical investigation. Infrared (IR) spectrum and antibacterial activity of MAE were carried out. Results: The results show that the percentage extract is different in the different solvents and also differs in phytochemical constituents. Phytochemicals present in the MAE also confirmed by IR spectroscopy. MAE is active against bacteria. Conclusion: The phytochemicals present in C. sativum is confirmed by IR spectrum and these phytochemicals responsible for antibacterial activity.